MENINGKATKAN KESADARAN MASYARAKAT SEJAK DINI MELALUI SIMMULASI BENCANA GEMPA BUMIDI DESA WOTGALIH, LUMAJANG - Ajie Dhohan; Tasya Wahyu Ramadani; Laras Setyowati; Akhfad Al Farabi; Edo Wahyudi , Kalvin; Putri, Vadila Mulia; Rukmana, Sarah Nurmala Putri; Agustia Putri, Elsa Sabrina; Rahmasari, Ayu (CV. Era Digital Nusantara, 2022)
Lumajang is one of the areas on the island of Java that has the risk of an earthquake and tsunami. Lumajang Regency is close to the confluence of the Eurasian and Australian plates with a distance of about 250 km from the coast. For 76 km the Lumajang area from Tempursari District to Yosowilangun is a coastal area that has the character of big and high waves up to about 3 meters. Based on these conditions, it is necessary to make efforts to reduce disaster risk through education so that it can be introduced earlier to all students. The number of fatalities when a disaster occurs can be caused by a lack of preparedness and low knowledge about earthquakes. Madrasah Ibtidayah Riyadus Sholihin is one of the schools located in Kab. Lumajang is precisely in Wotgalih Village. So far, there have been no socialization activities regarding earthquakes and mitigation as well as simulations when an earthquake occurs in schools for students. Therefore, East Java UPN